A new species of Helminthosporium (Massarinaceae, Pleosporales) from Taiwan - Kuo, Chang-Hsin; Hsieh, Sung-Yuan; Goh, Teik-Khiang (Phytotaxa, 2025)
Helminthosporium taiwanense sp. nov., isolated from a submerged decaying woody twig in a freshwater stream in Taiwan, is described and illustrated. While morphologically similar to Ellismarsporium due to its production of cylindrical conidia in short chains, multi-locus phylogenetic analyses based on a combined dataset of ITS, LSU, SSU, rpb2, and tef1-α sequences revealed it to be a distinct and undescribed species of Helminthosporium. The morphological boundaries and phylogenetic placement of the genus Ellismarsporium are discussed in light of this discovery.